Law on Environmental Protection in Burial Activities: Practice and Some Recommendations for Improvement - Huan, Tran Linh; Thuy Trang, Dang Thi (VNU Journal of Science: Legal Studies; Vol 38 No 3DO - 10.25073/2588-1167/vnuls.4430, 2022)
Environmental protection in burial activities is one of the key requirements to ensure the environment to be not affected by the negative impacts of burial activities. Currently, environmental protection requirements in burial activities have been governed by legal provisions, however, due to the influence of the long-standing habits and customs, along with the limitations of legal provisions on this issue, environmental protection in burial activities has not been guaranteed. This article focuses on i) clarifying the need to protect the environment in burial activities by the law, ii) on this basis, stating, analyzing and evaluating the current legal status on the matter, iii) finally, making some recommendations for improvement of the law.